Fertility Treatments in the United States: Improving Access and Outcomes. Issue 2 (August 2016) - Kissin, Dmitry M.; Boulet, Sheree L.; Jamieson, Denise J.
Abstract : The recently released National Public Health Action Plan for the Detection, Prevention, and Management of Infertility calls for better access to high-quality infertility services and improved safety of fertility treatments. Both assisted reproductive technology (ART) and non-ART fertility treatments have allowed millions of patients worldwide to overcome infertility—a disease of the reproductive system and important public health issue. However, there are substantial disparities in access to effective treatments in the United States, largely attributable to high out-of-pocket costs, especially for ART. Moreover, the outcomes of fertility treatments are often complicated by the large proportion of multiple births with substantial health risks for both neonates and mothers. Prevention of multiple births is difficult during non-ART fertility treatments but can be effective with single-embryo transfer during ART. Several U.S. states have enacted legislative mandates that require private insurers to cover some portion of the costs associated with fertility treatments and thus reduce the financial pressure to transfer multiple embryos during ART. Although studies have shown that insurance coverage reduces per-cycle multiple births to a certain degree, states with insurance mandates have more ART-related multiple births attributable to substantially larger number of ART-conceived neonates. Experience from other countries shows that access to ART can be improved without concomitant increases in multiple births by providing reimbursement for ART in combination with restrictions on the number of embryos transferred per cycle. Such approaches may or may not be successful in the United States with its unique and complex health care system. Abstract : Reimbursement for assisted reproductive technology linked to restrictions on the number of embryos transferred per cycle may alleviate disparities in access and improve treatment outcomes.